From Power Balance to Dominant Faction in Xi Jinping's China. (21st December 2021) - Choi, Eun Kyong; Givens, John Wagner; MacDonald, Andrew
Abstract: Many China watchers argue that Xi Jinping has concentrated power in his own hands in a manner unprecedented since the death of Mao Zedong and Deng Xiaoping. This article tests the extent of Xi's power consolidation by comparing the strength of his faction during his time in power to similar periods under his two immediate predecessors, Jiang Zemin and Hu Jintao. Furthermore, we investigate whether a dominant faction is emerging under Xi Jinping, replacing the power balancing between factions that was the norm throughout the reform era. Analysing factional affiliations of Chinese leaders in the top four ranks, we find that Xi has formed a dominant faction. Through statistical analysis of the promotion chances of provincial leaders, we find that Xi has been unusually successful when compared to previous leaders at promoting his clients. This suggests that Xi has boosted the power of his faction by elevating provincial leaders to an extent not seen since the death of Mao and Deng.